2016
DOI: 10.1021/acssuschemeng.6b00956
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Composite Films from Chitosan and Lignin: Antioxidant Activity Related to Structure and Moisture

Abstract: International audienceComposite films based on chitosan and lignin biopolymers were investigated for their mechanical, barrier, surface, and antioxidant properties and linked to an extensive microscopic analysis of their external and internal structure. In particular, the fluorescence properties of lignins were exploited, using two-photon microscopy, to achieve a 3D representation of its distribution within the chitosan matrix. The lignin incorporation generated small aggregates homogeneously distributed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 55 publications
1
67
0
Order By: Relevance
“…However, with 100 mg of CMC/ligninbased films no significant improvement in the RSA was observed with the increment of the reaction time. The antioxidant capacity can be attributed to some lignin groups presents in the surface with recognized antioxidant activity or to the migration of some of these free active molecules into the solution, such as monomers and oligomers, as well as other free phenols that could be present in the lignin samples, since lignins, as high molecular weight polymers, present low mobility (Crouvisier-Urion et al, 2016). Aadil et al (2016a) found that the free radical scavenging capacity of the gelatin/lignin films increased with the increase in lignin content, achieving 67.51% RSA (IC 50 111.10 μg/mL) in the water soluble fraction of film containing 40% lignin (the highest concentration).…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, with 100 mg of CMC/ligninbased films no significant improvement in the RSA was observed with the increment of the reaction time. The antioxidant capacity can be attributed to some lignin groups presents in the surface with recognized antioxidant activity or to the migration of some of these free active molecules into the solution, such as monomers and oligomers, as well as other free phenols that could be present in the lignin samples, since lignins, as high molecular weight polymers, present low mobility (Crouvisier-Urion et al, 2016). Aadil et al (2016a) found that the free radical scavenging capacity of the gelatin/lignin films increased with the increase in lignin content, achieving 67.51% RSA (IC 50 111.10 μg/mL) in the water soluble fraction of film containing 40% lignin (the highest concentration).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Several works have incorporated water soluble lignin, such as lignosulphonates and alkali lignins in different biopolymers (Aadil et al, 2016a;Aadil et al, 2016b;Núñez-Flores et al, 2012Bhat et al, 2013;Miranda et al, 2015;Shankar et al, 2015;Crouvisier-Urion et al, 2016. Aadil and co-authors (2016a,b) reported that alkali lignin reduced the water affinity of alginate and gelatin films, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This method can overcome the severe overlap of signals and reduce errors in signal quantification due to differential line widths, quantitative abundance of S/G/H units, hydroxycinnamates, and tricin units, as well as various types of side chain substructures by selecting the proper internal standard reference signals [93]. Other combinations of NMR techniques were also reported; for instance, the existence of low energy dipole-dipole interactions and the absence of covalent bond between lignin and chitosan could be revealed clearly by solid-state 1 H- 13 C CP/MAS NMR [94].…”
Section: Assignmentsmentioning
confidence: 99%
“…This has another positive effect, as a part of the agro-industrial by-products will become an economical and practical source of potent antioxidants [11,12]. Crouvisier-Urion et al [13] reported that the incorporation of lignin from wood extraction into chitosan film provided to the film a radical scavenging activity, essentially governed by a surface activity mechanism; and with high-pressure homogenization processing, could also increase the hydrophobicity of chitosan-lignin film, which can be useful in application [14]. Hargens-Madsen et al [15] used tocopherols in the edible film to improve precooked meat quality.…”
Section: Introductionmentioning
confidence: 99%